2019
DOI: 10.1088/1741-4326/ab2bd3
|View full text |Cite
|
Sign up to set email alerts
|

Density compensation and stored energy recovery in resonant magnetic perturbation suppressed edge-localized mode H-mode plasmas using pellet fueling on EAST

Abstract: The fueling of plasmas using frozen pellets in steady-state quiescent H-mode plasmas with edge-localized modes (ELMs) suppressed by external magnetic perturbations (RMPs) was successfully demonstrated on the EAST tokamak in plasmas with similar shapes to those in ITER with q 95 ~ 3.8, and triangularity δ ~ 0.45. During the fully suppressed-ELM phase using RMPs, the plasmas were refueled by deuterium pellets with a frequency of 5 Hz from ~40 cm above the mid-plane on the low field side. The results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…One typical shot #93536 is shown in figure 4. In this discharge, each frozen deuterium pellet containing about (1.03 ± 0.01) × 10 20 particles is injected from the low field side at about 0.4 m above the mid-plane with a velocity of about 100 m s −1 and a frequency of 10 Hz [15,38]. With these parameters, a simple modelling method described in [39] is applied to this EAST discharge and result predicts that the highest density increase caused by the pellet is around located ρ t = 0.88 as shown in figure 5(a).…”
Section: Pellet Injection During Elm Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…One typical shot #93536 is shown in figure 4. In this discharge, each frozen deuterium pellet containing about (1.03 ± 0.01) × 10 20 particles is injected from the low field side at about 0.4 m above the mid-plane with a velocity of about 100 m s −1 and a frequency of 10 Hz [15,38]. With these parameters, a simple modelling method described in [39] is applied to this EAST discharge and result predicts that the highest density increase caused by the pellet is around located ρ t = 0.88 as shown in figure 5(a).…”
Section: Pellet Injection During Elm Suppressionmentioning
confidence: 99%
“…Experiments in DIII-D showed that injecting pellets trigger frequent ELMs for full ELM suppressed H-modes while reduce the number of ELM events for partially ELM suppressed H-modes [14]. Similarly, previous experiments in EAST showed that injecting pellets into an ELM-suppressed H-mode with n = 2 RMPs returns the plasma to an ELMmitigated state [15].…”
Section: Introductionmentioning
confidence: 95%
“…One of the ELM control techniques is the application of external resonant magnetic perturbations (RMPs) [3][4][5][6] and such a system is planned on ITER [7]. Both pellet fuelling and RMPs act on the plasma periphery and therefore it is not surprising that these actuators are coupled as seen on DIII-D [3,[8][9][10], ASDEX Upgrade [11][12][13][14], MAST [15,16] and EAST [17]. This coupling takes the form of two effects.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 1(c) and (d) show the fitted electron temperature and density profiles before pellet injection. In this discharge, deuterium pellets are injected horizontally from the low field side (LFS), at about 0.4 m above the mid-plane, with a velocity of about 100 m s −1 [55]. In addition to the LFS-horizontal (LFS0.4) injection case, we also consider in our simulations the LFS-vertical (LFSv) injection case and the LFS-midplane (LFSm) horizontal injection case as shown in figure 1(a).…”
Section: Simulation Setupmentioning
confidence: 99%